COMPETENCIES OF THE FUTURE IN LIGHT OF THE CHANGES TAKING PLACE IN LARGE-SIZED COMPANIES - Miętkiewicz, Monika; Brzychcy, Katarzyna; Ziemkiewicz-Gawlik, Ilona; Jaroszewski, Karol (Management and Administration Journal, 2024)
The reality of the labour market is that changes are determined by both internal and external factors. The COVID-19 pandemic and the Russo-Ukrainian War doubtlessly resulted in a significant transformation of the labour market. The consequences of both events belong to external factors, where the expectations of both employers and employees, as well the offers being made by both groups participating in the labour market, clashed anew, revealing the existing competencies and deficits in their scope. Given the aim of the article, the authors will focus primarily on the conditions created by employers in large-sized companies, and their influence on the reinforcement and development of competencies of the future. The conducted survey studies indicate the necessity to introduce changes in the process of work organisation; and of the kind which will foster the development of competencies of the future. The studies were conducted taking into account the social changes in the external environment of organisations and the changes which were imposed on employers, remote work among others, in response to the changing environment. Thus, the issues raised in the studies, apart from competencies of the future, include organisational changes faced by the employees. Based on the obtained results recommendations were formulated.